The legacy of structural racism: Associations between historic redlining, current mortgage lending, and health. (June 2021) - Lynch, Emily E.; Malcoe, Lorraine Halinka; Laurent, Sarah E.; Richardson, Jason; Mitchell, Bruce C.; Meier, Helen C.S.
Abstract: Structural racism, which is embedded in past and present operations of the U.S. housing market, is a fundamental cause of racial health inequities. We conducted an ecologic study to 1) examine historic redlining in relation to current neighborhood lending discrimination and three key indicators of societal health (mental health, physical health, and infant mortality rate (IMR)) and 2) investigate sustained lending disinvestment as a determinant of current neighborhood health in one of the most hypersegregated metropolitan areas in the United States, Milwaukee, Wisconsin. We calculated weighted historic redlining scores from the proportion of 1930s Home Owners' Loan Corporation residential security grades contained within 2010 census tract boundaries. We combined two lending indicators from 2018 Home Mortgage Disclosure Act data to capture current neighborhood lending discrimination: low lending occurrence and high cost loans (measured via loan rate spread). Using historic redlining score and current lending discrimination, we created a 4-level hierarchical measure of lending trajectory. In Milwaukee neighborhoods, greater historic redlining was associated with current lending discrimination (OR = 1.73, 95%CI: 1.16, 2.58) and increased prevalence of poor physical health (β = 1.34, 95%CI: 0.40, 2.28) and poor mental health (β = 1.26, 95%CI: 0.51, 2.01). Historic redlining was not associated with neighborhood IMR (β = −0.48, 95%CI: −2.12, 1.15). A graded association was observed between lending trajectory and health: neighborhoods with high sustained disinvestment had worse physical and mental health than neighborhoods with high investment (poor physical health: β = 5.33, 95%CI: 3.05, 7.61; poor mental health: β = 4.32, 95%CI: 2.44, 6.20). IMR was highest in 'disinvested' neighborhoods (β = 5.87, 95%CI: 0.52, 11.22). Our findings illustrate ongoing legacies of government sponsored historic redlining. Structural racism, as manifested in historic and current forms of lending disinvestment, predicts poor health in Milwaukee's hypersegregated neighborhoods. We endorse equity focused policies that dismantle and repair the ways racism is entrenched in America's social fabric. Highlights: Examined structural racism in the housing market, historical redlining and current lending discrimination, on neighborhood health. Historic redlining score was associated with current lending discrimination and neighborhood health indicators. Sustained disinvestment over 80 years was associated with poor neighborhood health outcomes.